Subtle ocular motor deficits in people with chronic whiplash associated disorder compared to healthy controls - Callan, Brad; Vintimilla, Antonio; Gulla, Nicholas (Frontiers in Neurology, 2025)
IntroductionMore than 50% of people who are diagnosed with whiplash-associated disorder (WAD) will report symptoms 12 months and beyond after their initial onset. However, many signs and symptoms, such as dizziness, emotional lability, confusion, ocular movement abnormalities, and balance deficits, may not be directly attributed to the cervical spine and may be more consistent with post-concussive syndrome (PCS).MethodsA total of 15 people with chronic (>3 months) WAD and 15 age-sex match controls were recruited. They were evaluated on clinical tools commonly used to assess signs and symptoms associated with concussion and PCS, including self-report symptoms, balance, cognition, and vestibular-ocular assessments. All scores were assessed for differences between the two groups, and effect sizes were recorded.ResultsAll testing, except for balance, demonstrated significant differences between the groups. Within the ocular motion, 31/34 variables moved less efficiently in the WAD group. Using an exact binomial paired sign test, the likelihood of all eight ocular composite groups being less efficient in the WAD group is reported as p = 0.008.DiscussionPatients with chronic WAD demonstrate subtle but significant differences in ocular movement when compared to a control group. They also demonstrated significant differences on measures commonly used in the assessment of PCS despite never being diagnosed with it. These differences may contribute to some of the ongoing disability burden that this population commonly reports.